(3cJGH KdGKjGJ GdCaYGds - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eMeO eUHGM GdYeQi GdMGeOi GdTGaYi GdWQGHdSi GdGRgQi s)
(3ChdgG (B:s
(3bGd TjNfG gPG cJGH CPcQ ajg Ef TGA Gddg JYGdi eG JjSQ ef KdGKjGJ GdGaYGd Gdebhd ajgG CaYd Ch oCaYd HeYfi hGMO eQJHkG Ydi MQha GdeYLe s
(3BNQgG (B:s
(3aUd LeY ajg GdCaYGd GdJi GNJdaJ KdGKjJgG hQHGYJjgG HHfGA CMOgeG GdaGYd hGdGNQ ddeaYhd Je GdcJGH HMeO Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs